Ipsilateral breast tumor recurrence after breast-conserving therapy. Issue 8 (August 2010) - Panet-Raymond, Valerie; Truong, Pauline T; Watson, Peter H
In the modern era of breast-conserving therapy for early-stage breast cancer, ipsilateral breast tumor recurrence (IBTR) represents an increasingly common clinical dilemma. Two kinds of IBTRs have been described: true recurrences, which represent regrowth of uneradicated initial disease, and new primaries, which may be distinct from the index lesion in histology and location. Whether these two entities have different biologies and survival prognoses remains unclear. This article will examine contemporary clinical and pathologic methods to distinguish true recurrence from new primary tumors, focusing on available published data from prospective and retrospective studies. Current challenges and future avenues are discussed for developing a standardized, reproducible classification system for different types of IBTR that may be used in the clinical setting to prognosticate and individualize treatment for patients following in-breast recurrences.